2009
DOI: 10.3109/08977190903407365
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal phenotype in mice overexpressing a heparin-binding EGF-like growth factor transgene in enterocytes

Abstract: Primary objective Heparin-binding EGF-like growth factor (HB-EGF) protects the intestine from damage in animals. Future clinical trials of HB-EGF may involve administration of repeated doses of HB-EGF. Since HB-EGF activates EGF receptors which have been implicated in tumor development, we examined the effects of HB-EGF overexpression in the intestine. Research design We generated transgenic (TG) mice in which the human HB-EGF gene is driven by the villin promoter to overexpress HB-EGF along the crypt-villou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…We have shown that endogenous HB-EGF is increased in intestinal epithelial cells (IEC) in response to anoxia/reoxygenation and in intestine in response to I/R injury (11). We have also shown that HB-EGF knockout (KO) mice have increased intestinal injury in animal models of intestinal I/R (12), hemorrhagic shock and resuscitation (HS/R) (13) and necrotizing enterocolitis (NEC) (14), and that HB-EGF transgenic mice have decreased intestinal injury after HS/R (15) and improved intestinal anastomotic wound healing (unpublished data). Lastly, administration of exogenous HB-EGF protects the intestines from injury in animal models of I/R, HS/R and NEC (16, 17, 18).…”
Section: Introductionmentioning
confidence: 91%
“…We have shown that endogenous HB-EGF is increased in intestinal epithelial cells (IEC) in response to anoxia/reoxygenation and in intestine in response to I/R injury (11). We have also shown that HB-EGF knockout (KO) mice have increased intestinal injury in animal models of intestinal I/R (12), hemorrhagic shock and resuscitation (HS/R) (13) and necrotizing enterocolitis (NEC) (14), and that HB-EGF transgenic mice have decreased intestinal injury after HS/R (15) and improved intestinal anastomotic wound healing (unpublished data). Lastly, administration of exogenous HB-EGF protects the intestines from injury in animal models of I/R, HS/R and NEC (16, 17, 18).…”
Section: Introductionmentioning
confidence: 91%
“…Although growth factors can promote wound healing, they are also involved in tumor progression. In preparation for human clinical administration of HB-EGF, we have developed and studied HB-EGF transgenic (TG) mice that specifically over-express HB-EGF in the gastrointestinal tract from the stomach to the colon under the direction of the villin promoter [94]. Upon examining the intestines of these HBEGF TG mice from newborn to geriatric ages, we were unable to identify any intestinal abnormalities, polyps or tumors [94].…”
Section: Effects Of Hb-egf During Intestinal Injurymentioning
confidence: 99%
“…These mice were designed to specifically overexpress the human HB-EGF precursor (proHB-EGF) in the intestine using a 12.4 kb villin regulatory and promoter sequence to drive human proHB-EGF gene expression. [15] The villin promoter ensures the constant expression of HB-EGF throughout the entire intestine from the duodenum to the colon, throughout the entire crypt-villous axis.…”
Section: Introductionmentioning
confidence: 99%